PENGARUH METODE PEMICUAN TERHADAP PERUBAHAN PERILAKU BUANG AIR BESAR SEMBARANGAN PADA MASYARAKAT KELURAHAN KAUMAN KIDUL KOTA SALATIGA - Pudjaningrum Pudjaningrum; Nur Endah Wahyuningsih; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2016)
The practice of open defecation is one of problems in sanitation and healthy hygienic behavior at Kelurahan Kauman Kidul’s community Salatiga. Recorded 79 families that still practice open defecation. Acces to latrines, which reached 68,78% compounded by floods that began often occurs after the construction of toll road aggravate the sanitary condition at Kelurahan Kauman Kidul. Permenkes No. 3 In 2014 about Community Based on Total Sanitation ( STBM ) is an approach to changing behavior hygienic and sanitary through community empowerment by means of triggering. The purpose of this research was to analyze the effect of triggering methods on the behavior of open defecation  at Kauman Kidul’s community Salatiga. This research uses a pre-experimental design with one group pre-test post-test design. The population in this research is Kauman Kidul communities that still practice open defecation  with a whole as samples based on inclusion and exclusion criteria. For analyzed is using univariate and bivariate by paired t test for normally distributed data and Wilcoxon test for abnormal distributed data with a significance level of 0.05. The results of the research showed that there was a significant differences in knowledge, attitudes and practices of the respondent about defecation behavior before and after the intervention method gets triggered with a p value less than 0.05. Therefore, this method is appropriate to proceed for areas where the population is still found practicing open defecation.